1991
DOI: 10.1109/55.119185
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of enhanced performance of an InP/InGaAs heterojunction phototransistor with a base terminal

Abstract: Abstruct-The optical gain and the small-signal frequency response of an InP/InGaAs heterojunction phototransistor (HPT) with a base terminal are investigated in detail for the first time. When operated under an optimally chosen external base current, the optical gain is enhanced more than five times over that of the same device operated as a two-terminal device, over a 17-dB range of input optical power. The small-signal 3-dB bandwidth of the three-terminal device is enhanced 15 times over that of the two-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 5 publications
2
41
1
Order By: Relevance
“…Although much work has been done on high-speed phototransistors, [85] a classic design conflict exists between the simultaneous optimization of high-frequency performance and optical coupling efficiency. In lumped-element heterojunction phototransistors (HPTs), the devices need to be scaled down in size for high-speed operation.…”
Section: Traveling-wave Heterojunction Phototransistorsmentioning
confidence: 99%
“…Although much work has been done on high-speed phototransistors, [85] a classic design conflict exists between the simultaneous optimization of high-frequency performance and optical coupling efficiency. In lumped-element heterojunction phototransistors (HPTs), the devices need to be scaled down in size for high-speed operation.…”
Section: Traveling-wave Heterojunction Phototransistorsmentioning
confidence: 99%
“…This paper concems a physics-based quantitative analysis of the optical response of the HBT, supported by experimental verification. Although Chandrasekhar et al [6] have clearly shown the superiority of 3-terminal compared to 2-terminal devices, we believe that such performance can be further improved by taking advantage of the internal photoconductive effect when the transistor is biased with a true current source. The following sections describe the different mechanisms associated with the photoresponse depending on the biasing configuration.…”
Section: Introductionmentioning
confidence: 93%
“…This current is more significant than ISS and is usually large in heterojunction devices due to the strong and dominant recombination in the base emitter space charge region (Campbell and Ogawa, 1982;Chandrasekhar et al, 1991;Lin et al, 2000;Tan et al, 2004;Park et al, 2010). As we shall see shortly, scaling of the injector with respect to the trapping layer reduces this recombination current ideally by the ratio of trapping layer to injector area (AB/AE).…”
Section: Impact Of the Unique Three-dimensional Geometry On The Perfomentioning
confidence: 99%